The values of independent hip-hop in the post-golden era : hip-hop’s rebels (2019)
I remember back in 2008 Lupe Fiasco released the song “Hip-Hop Saved My Life.” He was telling a story of a rapper facing the everyday struggles of making it in hip-hop, getting out the hood, providing for a family, and ultimately growing as a person. Like Lupe’s song, many messages in hip-hop gave me something to relate to growing up, facing many of the same struggles that a person of color in urban America faces today. But my story was also unique. As a frst generation US-born Filipino in San Diego, CA, I grew up in a culture that either stereotypically envisioned us as smart and passive or just completely invisible. All the meanwhile, many Filipinos are just trying to get by, assimilating into a culture that has colonized them, and creating a different legacy for the next generation. What I saw in hip-hop was a place where many voices and stories could be heard, including my own. I knew I did not have the skills or talent to become a musician, but I wanted to tell my story in a different way. At San Diego State University, I took an Introduction to Sociology course with Professor Jung Min Choi and it allowed me to connect the music I was listening to with what I was learning in the classroom. And thus, this project began.